2015
DOI: 10.4155/fso.15.15
|View full text |Cite
|
Sign up to set email alerts
|

Selective nuclear localization of siRNA by metallic versus semiconducting single wall carbon nanotubes in keratinocytes

Abstract: Background:The potential use of carbon nanotubes (CNTs) in gene therapy as delivery systems for nucleic acids has been recently recognized. Here, we describe that metallic versus semiconducting single-wall CNTs can produce significant differences in transfection rate and cellular distribution of siRNA in murine PAM212 keratinocytes.Results/Methodology:The results of cell interaction studies, coupled with supportive computational simulations and ultrastructural studies revealed that the use of metallic single w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Huzil et al compared metallic SWCNTs with semiconducting CNTs on siRNA delivery; the results in murine PAM212 keratinocytes showed that metallic SWCNTs can be transferred into the nucleus, while the transport of semiconducting CNTs was limited since they could only only enter the cytoplasm. 102 This result suggests that metallic SWCNTs can provide a specific target to the nucleus and has a potential to apply in gene delivery. In addition, Tan et al explored silibinin-loaded CNTs with surface coating surfactant and polymer in mouse fibroblast cells, proved its biocompatibility was improved significantly, and the results also showed the sustained release effect of this drug delivery system.…”
Section: Carbon Nanotubesmentioning
confidence: 88%
“…Huzil et al compared metallic SWCNTs with semiconducting CNTs on siRNA delivery; the results in murine PAM212 keratinocytes showed that metallic SWCNTs can be transferred into the nucleus, while the transport of semiconducting CNTs was limited since they could only only enter the cytoplasm. 102 This result suggests that metallic SWCNTs can provide a specific target to the nucleus and has a potential to apply in gene delivery. In addition, Tan et al explored silibinin-loaded CNTs with surface coating surfactant and polymer in mouse fibroblast cells, proved its biocompatibility was improved significantly, and the results also showed the sustained release effect of this drug delivery system.…”
Section: Carbon Nanotubesmentioning
confidence: 88%
“…Carbon nanotubes (CNTs) are also used for nucleic acid delivery systems in gene therapy. Huzil et al [ 63 ] studied the effect of metallic versus semiconducting single-wall CNTs on the rate of transfection and siRNAcellular distribution in keratinocytes of murine PAM212. The data on the interaction of cellsand ultrastructural studies showed that CNTs’ metallic single wall was involved in the delivery of siRNA both into the nucleus and cytoplasm of keratinocytes, whereas semiconducting CNTs showed delivery in only the cytoplasm, suggesting that CNTs can be used in the development of nonviral gene delivery systems in the near future.…”
Section: Types Of Nanoparticlesmentioning
confidence: 99%
“…Molecular modeling and experimental data indicates that complex mixture of supramolecular interactions, including electrostatic, hydrogen bonding, π-stacking and van der Waals interactions play a role in the binding of nanotubes to DNA [53][54][55][56][57][58][59][60][61], and RNA [57,[62][63][64][65]. An elegant study including computational simulations and in vitro cell culture studies with keratinocytes highlighted the role of the electronic structure of nanotubes on RNA binding and delivery, with metallic SWNTs delivering siRNA into the nucleus of keratinocytes, whereas semiconducting SWNTs transported siRNA only to the cytoplasm [66]. Interestingly, hydrophobic interactions that facilitate DNA binding to anionic carboxy-functionalized MWNTs yield complexes that were shown to transfect the DNA more effectively into Nile Tilapia (Oreochromis niloticus) spermatogonial stem cells than either electroporation or Lipofectamine® 2000 [67].…”
Section: Carbon Nanotubesmentioning
confidence: 99%